PENERAPAN METODE BAYANI DALAM PENEMUAN HUKUM MEROKOK - Bakhtiar, Bakhtiar (Turast: Jurnal Penelitian dan Pengabdian, 2020)
The process of determining the smoking ban fatwa published by Muhammadiyah uses a method based on a linguistic approach. This legal fatwa reaps pros and cons in society. There are those who think it is not wise because smoking is related to the lives of many people and is the biggest source of income for the country. There are those who think smoking causes danger and threatens the existence of life. This study aims to explain how the implementation of the Bayani method used by Muhammadiyah in determining smoking law fatwas?. Explain how the factors that led Muhammadiyah to use the bâyanÎ method?. Explain how the implications of using the baby method in avoiding the dangers and threats of smoking?. This research is qualitative descriptive by using documents as data containing epistemological values, functions, conditions and social relationships with the fatwa of the smoking law. The results of this study indicate, first, that the bayânÎ method used by Muhammadiyah is not limited to the approach of linguistic principles, but also considers scientific facts and social facts found and reported by experts. Second, the use of the bayânÎ method is due to the factors of demand and compliance with the articles of association and manhaj tarjih in responding to the phenomena of dangers and threats posed by cigarettes. Third, the use of the bayânÎ method has implications in preventing the public from the threats and dangers posed by smoking because it is expressly prohibited by syara